Results of a multicenter SPECT study with [123I]-Iodolisuride in extrapyramidal syndromes. - Ribeiro, MJ (2001)
The main objective of the present multicenter study was to evaluate -Iodolisuride (-ILIS) as a radioligand for dopamine receptors in patients (pts) with extrapyramidal diseases when using g-cameras of different types. 45 pts (28M, 17F) were studied in 2 centers (23+22 pts) and were divided in 2 groups: group I (n=28 age=66.8±3.5 years): idiopathic Parkinson’s disease; group II (n=17, age=57.5±7.1 years): other extrapyramidal syndromes. -ILIS (1.7 to 2.8 MBq/kg) was injected after informed consent. Single photon emission computed tomography (SPECT) studies were performed with a single head -camera (-camera A, GE 400AC*, 24 studies 1 hr p.i.), a dual head -camera (-camera B, Helix Elscint*, 15 studies 1hr to 2.5hr p.i.), a triple head -camera (-camera C, Neurocam GE*, 12 studies 45min to 2hr p.i.) and a brain dedicated annular detector (-camera -camera D, Ceraspect DSI*, 17 studies 1 to 3.5hr p.i.). Patients showed no undesirable reactions. All SPECT images obtained with different -cameras contained sufficient information for clinical interpretation and were qualitatively interpreted according to the visualization of basal ganglia (or striata) alone (type 1), visualization of cerebral cortex alone (type 2) and visualization of both basal ganglia and cerebral cortex (type 3) on the transversal slices. Striatal/frontal cortex ratios (S/FC) were calculated from standardized geometrical regions of interest. In group I, 45/45 SPECT images were classified as type 1 or type 3. In group II, 18/23 SPECT were classified as type 2 or 3. With any -camera, S/FC values were significantly higher in group I than in group II: -camera A: S/FC=1.48±0.20 vs. 1.26±0.25 (p=0,036), -camera B: S/FC=2.32±0.27 vs. 1.75±0.70 (p=0.025), -camera C: S/FC=1.55±0.22 vs. 1.34±0.15 (p=0.033), -camera D: S/FC=3.07±1.30 vs. 2.11±0.66 (p=0.039). We conclude that -ILIS imaging with any -camera provides functional information on striatal dopaminergic synapses in patients with extrapyramidal degenerative disease and could be useful in the differential diagnosis between Parkinson’s disease and other extrapyramidal syndromes. However, clinical use of -ILIS will require normalization and standardization of imaging and data processing procedures.